Penurunan Fungsi Saraf Olfaktorius (CN1) pada Mencit (Mus musculus) Akibat Induksi Natrium Siklamat Berlebih - Putri Cahyaningrum; Riyanto Riyanto (Yayasan Literasi Sains Indonesia, 2026)
The use of sodium cyclamate, an artificial sweetener, as an additive in food and beverage production is commonly found among vendors around schools and campuses. Artificial sweeteners such as sodium cyclamate are often used as substitutes for sugar to reduce production costs. Although its dosage has been regulated by government and health authorities, these regulations are frequently ignored by vendors who prioritize profit without considering product quality and nutritional value. Excessive use of artificial sweeteners, particularly sodium cyclamate, can have harmful health effects. Several studies indicate that excessive consumption may damage nerve cells. Therefore, this study aims to determine the effect of excessive sodium cyclamate consumption on the decline of olfactory nerve function (CN I) in mice (Mus musculus). The dosage used was adjusted according to BPOM regulations for humans, which is 11 mg/kg body weight, then converted for mice using the Laurence conversion table. Twelve male Swiss Webster mice were divided into four groups: a control group and three treatment groups (P1: 0.55 mg/kg BW, P2: 1.1 mg/kg BW, P3: 1.65 mg/kg BW), each consisting of three mice. Sodium cyclamate was administered for 25 days to ensure systemic exposure. An ammonia scent test was then conducted to assess olfactory nerve function decline. The results showed that higher doses were associated with greater reduction in ammonia detection ability, indicating decreased olfactory nerve function (CN I).